Mechanics of materials - Beer, Ferdinand P.; Johnston, E. Russell (Elwood Russell); DeWolf, John T.; Mazurek, David F.; Sanghi, Sanjeev (McGraw-Hill, 2020)
A strong conceptual understanding is essential for solving problems successfully. This edition helps instructors and students achieve this goal by providing strong understanding and logical analysis of the concepts using SI units, which also helps identify the applications in designing actual engineering structures and machine components.